POWER EXERCISE FACING THE COMPLEXITY OF RELATIONS IN MEDICAL-HOSPITAL AND NURSING SETTINGS - Ivete Palmira Sanson Zagonel (Universidade Federal do Paraná, 1996)
This purpose is a thought - provoking study on the exercise of disciplinary power in medical - hospital and nursing settings, historically focusing on the onset of medicine, hospitals and nursing. This purpose evidences the evolution of the nurse as a professional, his/ her submission to institucional or medical knowledge and the social appraisal attributed to nursing practice wich is closely connected with a cnventual, submissive way ofliving. In this context, nursing has strived to obtain a scientific status andhas tried to eliminate its solelyu practical nature. I have re-apprehended the importance of nursing centered on client´s care, its ultimate goal.